Tissue tropism and pathology of highly pathogenic avian influenza H5N6 virus in chickens and Pekin ducks. (September 2022) - Vreman, Sandra; Bergervoet, Saskia A.; Zwart, Rob; Stockhofe-Zurwieden, Norbert; Beerens, Nancy
Abstract: The highly pathogenic avian influenza (HPAI) H5N6 virus caused outbreaks on commercial poultry farms in the Netherlands in 2017–2018, holding chickens and Pekin ducks. Intravenous pathogenicity index (IVPI) tests confirmed the high pathogenicity of the virus. Tissues derived from birds from infected farms (natural infection) and IVPI tests (experimental infection) were used to compare histopathology and virus distribution in both poultry species. After natural infection in chickens, histopathologic changes were present in the respiratory tract and several internal organs in both chickens and Pekin ducks. Viral antigen expression in the tissues of chickens varied from that in ducks. Virus expression was found in epithelial, mononuclear and endothelial cells in chickens. In contrast to the major role infected endothelial cells seem to play in systemic infections of chickens, in ducks the number of infected endothelial cells was very limited. Therefore, endothelial cell infection likely does not play a major role in systemic infection and disease progression in HPAI H5N6 virus infected Pekin ducks. Highlights: Natural HPAI H5N6 virus infection was studied in two commercial poultry species Histopathologic changes were present in the respiratory tract and several internal organs in both chickens and Pekin ducks. Viral antigen expression in the tissues of chickens varied from that in ducks. In chickens virus expression found in epithelial, mononuclear and endothelial cells In Pekin ducks only limited virus expression in endothelial cells